Performance score variation between days at Australian national and Olympic women's artistic gymnastics competition - Bradshaw, E. J.; Hume, P. A.; Aisbett, B. (Journal of Sports Sciences, 2012)
We determined the inter-day variability in elite-standard women's artistic gymnastics competition scores. National (50 gymnasts for up to three days) and Olympic (24 gymnasts for up to five days) competition scores published in the public domain (Giant poster pull-out`, 2010, Gymnastics Australia, 2008) were evaluated using three statistical measures. Analyses of the inter-day differences in the mean scores as a percentage (MDiff%), coefficient of variation percentages for the mean score across both days (CV%), and Pearson correlation coefficients for the inter-day score (r) were interpreted using thresholds from trivial to large. National-class gymnasts' two-day performance variation was trivial for vault, small for floor and beam, and moderate for bars. When senior gymnasts competed for a third day the performance variation increased to moderate for vault. Across five days of Olympic competition there were trivial (e.g. CV%: vault = 0.8) to small (e.g. CV%: bars = 2.0) variations in performances between days on all apparatus. Olympians' performance score consistency is superior to senior, national-class competitors. The performance score consistency required for gymnasts who aspire to participate at the Olympics as a top-24 competitor is better than 3%.